2002
DOI: 10.1128/iai.70.8.4002-4008.2002
|View full text |Cite
|
Sign up to set email alerts
|

Up-Regulation of Fas (CD95) and Induction of Apoptosis in Intestinal Epithelial Cells by Nematode - Derived Molecules

Abstract: Infection by the intestinal nematode Nippostrongylus brasiliensis induces acceleration of apoptosis in the small intestinal villus epithelial cells in vivo. In the present study, we examined whether worm extract or excretory-secretory product induces apoptosis in the rat intestinal epithelial cell line IEC-6 in vitro. In the presence of worm extract or excretory-secretory product (>6 g/ml), IEC-6 cell growth was significantly suppressed, and there was a concomitant increase in the number of detached cells in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 29 publications
(34 reference statements)
1
9
0
Order By: Relevance
“…Whilst protozoan parasites inhibit host cell apoptosis attempting to perpetuate their life cycle within cells (Heussler et al, 2001;Lüder et al, 2001) it seems that extracellulary-living helminths modulate host apoptosis by its induction in target host immune cells. This has been proposed recently for intestinal nematodes, filariae, schistosomes and cestode Taenia crassiceps (Chen et al, 2002;Jenson et al, 2002;Kuroda et al, 2002;Lopez-Briones et al, 2003) and our data show that similar mechanism develops in turbellaria-bivalve system. Caspase positive reaction inferred by IHC in M. galloprovincialis was triggered in cases of turbellarian infestation, in contrast with hydroids, suggesting more complex host-parasite interaction and persistent attempts of the parasite to survive bivalve reaction.…”
Section: Discussionsupporting
confidence: 72%
“…Whilst protozoan parasites inhibit host cell apoptosis attempting to perpetuate their life cycle within cells (Heussler et al, 2001;Lüder et al, 2001) it seems that extracellulary-living helminths modulate host apoptosis by its induction in target host immune cells. This has been proposed recently for intestinal nematodes, filariae, schistosomes and cestode Taenia crassiceps (Chen et al, 2002;Jenson et al, 2002;Kuroda et al, 2002;Lopez-Briones et al, 2003) and our data show that similar mechanism develops in turbellaria-bivalve system. Caspase positive reaction inferred by IHC in M. galloprovincialis was triggered in cases of turbellarian infestation, in contrast with hydroids, suggesting more complex host-parasite interaction and persistent attempts of the parasite to survive bivalve reaction.…”
Section: Discussionsupporting
confidence: 72%
“…The stages of development may release substances that induce apoptosis in infected areas, similarly to that which occurs in rat intestinal epithelial cells infected with nematode‐derived molecules (Kuroda et al . ) or in human intestinal epithelial cells infected with Giardia intestinalis (Kofoid & Christiansen, 1915; Panaro et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Strikingly, during infection with E. scophthalmi, the active caspase-3-positive cells were located in the parasitized folds but were not necessarily in direct contact with the myxosporean. The stages of development may release substances that induce apoptosis in infected areas, similarly to that which occurs in rat intestinal epithelial cells infected with nematode-derived molecules (Kuroda et al 2002) or in human intestinal epithelial cells infected with Giardia intestinalis (Kofoid & Christiansen, 1915;Panaro et al 2007). Another reason would be an increase in the rate of epithelial cell turnover promoted by cytokines as a strategy to expel the parasites, as reported during infection with Trichuris trichuria in human (Cliffe et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…For example, secretory products released from schistosomulae of S. mansoni [35], adults of Nippostrongylus brasiliensis [36]and hookworm [37]dose-dependently induced apoptosis of immune cells. In addition, it has been shown that persistent cellular immunosuppression with a concomitant increasing load of parasites in vivo was closely related to enhanced apoptosis of T cells after in vitro stimulation of the parasite antigen [38].…”
Section: Discussionmentioning
confidence: 99%